A Literature Review: The Influence of Delegative Leadership Style on Employee Performance and Job Satisfaction - Andi Indriani Ibrahim; Syahbudin Adam; Hikma H. Rahman; Anita H. Hasyim; Nur Fadilah; Marsyanda Lanonci; Ulfa N. Yojo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Delegative leadership is a leadership style that grants subordinates broad autonomy to make decisions and take responsibility for their work. In modern organizations, this style is believed to foster self-confidence, participation, and performance. However, its effectiveness depends greatly on the leader’s ability to provide clear direction and support (Gunawan & Al Hariri, 2019). This study aims to review various research findings regarding the influence of delegative leadership on employee performance and job satisfaction through a comprehensive literature review (Fauzan & Santoso, 2024). Method: A literature review method was conducted by analyzing 20 scholarly articles published between 2014 and 2025 obtained from databases such as Google Scholar, ScienceDirect, and other academic sources (Pratama et al., 2024). Result: Most studies found that delegative leadership positively affects employee performance by improving responsibility, self-confidence, and intrinsic motivation. Furthermore, it enhances job satisfaction when accompanied by effective communication and role clarity (I Gusti Ayu Widari, Nengah Landra, 2025). Conclusion: Delegative leadership plays a significant role in creating a participative and productive work environment, though its success highly depends on organizational culture and employee maturity levels (Maarif, 2020)